(untitled) (Bioscience Journal, 2020)
Essential oils have emerged as an alternative to synthetic insecticides in the control of stored grain pests. The toxicity and repellency of the essential oils of four basil cultivars and three basil hybrids and the monoterpenes linalool, citral, and (E)-methyl cinnamate were evaluated in the stored grain pests Callosobruchus maculatus and Sitophillus zeamais. The essential oils of the cultivar Genovese and the hybrid ’Genovese’ x ’Maria Bonita’ were more toxic to C. maculatus. Conversely, the essential oils of the cultivar Sweet Dani and the hybrid ’Cinnamom’ x ’Maria Bonita’ were more toxic to S. zeamais. Among the monoterpenes, (E)-methyl cinnamate was the most toxic to both pests, taking 0.14 and 0.34 µL.mL-1 to kill 50% of the C. maculatus and S. zeamais populations, respectively. All essential oils from cultivars, hybrids, and monoterpenes were repellent to S. zeamais, except for (E)-methyl cinnamate. For C. maculatus, this effect was lower, being citral the most repellent compound. Results demonstrate the insecticidal potential of the essential oil of O. basilicum and its monoterpenes in the control of stored grain pests.